2005
DOI: 10.1126/science.1110324
|View full text |Cite
|
Sign up to set email alerts
|

Early Asymmetry of Gene Transcription in Embryonic Human Left and Right Cerebral Cortex

Abstract: The human left and right cerebral hemispheres are anatomically and functionally asymmetric. To test whether human cortical asymmetry has a molecular basis, we studied gene expression levels between the left and right embryonic hemispheres using Serial Analysis of Gene Expression (SAGE), and identified and verified 27 differentially expressed genes, suggesting that human cortical asymmetry is accompanied by early, striking transcriptional asymmetries. LMO4 is consistently more highly expressed in the right peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
274
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(305 citation statements)
references
References 22 publications
27
274
0
4
Order By: Relevance
“…Increased heritability over childhood and adolescence has been observed in cognitive traits such as IQ and prosocial behavior [Knafo and Plomin, 2006]. One likely contributor to changing heritability is agedependent gene expression Sun et al, 2005;Weickert et al, 2007]. Another potential factor is gene-environment correlation, which occurs when the same genes affect both a trait and relevant features of the environment, and also acts to increase heritability values [Kendler and Baker, 2007;Scarr and McCartney, 1983].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased heritability over childhood and adolescence has been observed in cognitive traits such as IQ and prosocial behavior [Knafo and Plomin, 2006]. One likely contributor to changing heritability is agedependent gene expression Sun et al, 2005;Weickert et al, 2007]. Another potential factor is gene-environment correlation, which occurs when the same genes affect both a trait and relevant features of the environment, and also acts to increase heritability values [Kendler and Baker, 2007;Scarr and McCartney, 1983].…”
Section: Discussionmentioning
confidence: 99%
“…Hulshoff Pol et al [2006] found evidence for significant heritability of gray and white matter density within several brain regions in a twin study of 258 adult subjects. There have been no previous studies of developmental changes in heritability of cortical features in humans, despite evidence of developmental changes in postnatal cortical structure [Gogtay et al, 2004] and postnatal gene expression [Plomin and Craig, 1997;Sun et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…41 ) It will also be interesting to compare the regulation of LRRTM1 longitudinally during the development of humans and other species, as the imprinted regulation may be restricted to certain developmental periods. 38 In addition, human genetic variation at this locus in nonclinical populations could be analyzed with dense marker genotyping, to test for evidence of selection, particularly with regard to the risk haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for hemispheric asymmetry in genetically influenced brain areas could be that certain genes are predominantly expressed in one hemisphere. For example, it was reported that the LM04 gene (essential for cortical development in mice) was more highly expressed in the right hemisphere than in the left [Sun et al, 2005].…”
Section: Discussionmentioning
confidence: 99%